Engineered Resilience for Complex Systems as a Predictor for Cost Overruns. Issue 2 (26th May 2016) - Roberts, Blake; Mazzuchi, Thomas; Sarkani, Shahram
ABSTRACT: The ever‐increasing complexity of large‐scale, ubiquitous systems, and internetworked Systems of Systems (SoS), have resulted in non‐linear challenges for systems engineering and program management such as interdependent, dynamic, and emergent behaviors that influence design and development cost. In order to invest, make decisions, and effectively manage technology developments, "should‐cost" estimates are used to baseline systems to what is considered affordable over the lifecycle. In addition to a higher likelihood for overrun, complex systems traditionally require major acquisitions, budgets, and development schedules where failure results in increased cost consequences. Behavioral properties (such as emergence) can influence performance resulting in dynamic and unpredictable effects on networked platform operation, system capability, and mission effectiveness. Data analyzed from 526 major weapons programs and from subject‐matter expert judgment are explored to propose: (1) a new approach to quantify these risks using prescriptive measures related to complexity, adaptability, and resilience, (2) identify leading indicators to reduce the likelihood of cost overrun, (3) suggest measurements based on research findings and systems heuristics to improve lifecycle cost estimation, and (4) present applications of Engineering Resilience to meet the growing complexity, interdependence, and scale of systems under constrained budgets with a growing demand for affordability.